Experience of Nurses in Carrying Out the Main Duties and Functions of Nurses at UPT Puskesmas Panamas, Kapuas Regency, in 2023 / 2024 - Ririn Charlina; Achir Yani Hamid; M. Syafwani (International Journal of Public Health, 2024)
This research explores the experiences of nurses in carrying out their main duties and functions at the Panamas Community Health Center. Qualitative methods with a phenomenological approach are used to gain an in-depth understanding of this phenomenon. Data was collected through in-depth interviews with 12 nurses selected by purposive sampling. Data analysis using the Colaizzi method produced five main themes: (1) Nurses' activities in health services, (2) Tasks carried out by community health center nurses, (3) The importance of good health program management, (4) Management of duties and authority in health services, and (5) Shortage of health and non-health personnel and multifunctionality in health services. Research results show that nurses often have to take over the roles of doctors, administrative staff, and pharmacists due to limited human resources even though these tasks should not be their responsibility. This causes nurses to lose focus in carrying out their main duties, nurses feel that their main role as care providers is disturbed. Nurses also run various health programs and serve as physician assistants, although these roles often exceed their duties. The importance of good health program management was emphasized, as many participants experienced difficulties in achieving targets, reporting and patient monitoring. Management of tasks and authority includes handover of tasks, delegation of daily tasks, and delegation of authority, however socialization to staff has not been comprehensive. Lack of human resources causes nurses to carry out multiple roles which hinders their professional development. This research recommends strengthening competency and further training for nurses, increasing legal awareness regarding the delegation of authority, integrating health management education in the nursing curriculum, as well as increasing the number and qualifications of human resources in community health centers.